Managing salespeople : a relationship approach - Hite, Robert E. (South-Western College, 1998)
This book is divided into four parts: Understanding the sales force environment; Planning for sales; Recruiting, training, and developing the sales force; Motivating, supervising, and evaluating the sales force; and The selling process.